Research Trends in Internet and Higher Education Journal: Blibiometric Analysis (Eurasian Journal of Learning and Academic Teaching, 2022)
Articles in the field of education have been widely researched and published in various journals, both local and international. Journals compete with each other to produce the best publications and have a positive impact on the development of the science under study. The purpose of this study is to provide information through visualization of various aspects of research trends in the journal Internet and Higher Education. This study analyzes Internet and Higher Education journals from 2015 to 2022, identifying the publications in each year, the most prolific authors, the most researched topics, and how interest in the relationships between topics develops. Bibliographic data was collected from the Scopus database of the Internet and Higher Education journal with a total of 208 documents which were analyzed using a bibliometric or scientometric approach